2012
DOI: 10.1111/j.1475-682x.2012.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

The Latina/o Racial and Citizenship Divide on Perceptions of the Influence of Immigrant Mobilizations*

Abstract: In spring 2006, the United States witnessed immigrant marches throughout the nation. Although Latina/os are often depicted as the “face” of the immigrant marches, we know little about how racial and citizenship statuses shaped Latina/os’ perceptions of how the marches influenced public perceptions of undocumented immigrants. Using logistic regression on data from the 2006 National Survey of Latinos, we find that Latina/os identifying as white are less likely to be supportive of the immigrant marches than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These historical issues are useful in examining contemporary intraracial relations impacting people of Mexican descent. Work on intraracial relations among Latinas/os has focused on the larger sociopolitical context that explains the relations among groups that share common racial experiences and ancestry (Gutierrez 1995; Ochoa 2004:5-6; Morales, Murga, and Sanchez 2013; Alba et al 2014; Dowling 2014). While work on intraracial relations has focused on the various aspects of nativity, class, phenotype, language, and culture shaping these relationships, less research has attended to the ways that white racism and white supremacy inevitably become embedded in the daily lives of Mexican Americans living along the US–Mexico borderlands (for notable exceptions see, Dowling 2014; Ochoa 2004; Vila 2000).…”
Section: Personal Reflexive Statementsmentioning
confidence: 99%
See 2 more Smart Citations
“…These historical issues are useful in examining contemporary intraracial relations impacting people of Mexican descent. Work on intraracial relations among Latinas/os has focused on the larger sociopolitical context that explains the relations among groups that share common racial experiences and ancestry (Gutierrez 1995; Ochoa 2004:5-6; Morales, Murga, and Sanchez 2013; Alba et al 2014; Dowling 2014). While work on intraracial relations has focused on the various aspects of nativity, class, phenotype, language, and culture shaping these relationships, less research has attended to the ways that white racism and white supremacy inevitably become embedded in the daily lives of Mexican Americans living along the US–Mexico borderlands (for notable exceptions see, Dowling 2014; Ochoa 2004; Vila 2000).…”
Section: Personal Reflexive Statementsmentioning
confidence: 99%
“…In the case of people of Mexican origin in the United States, immigration laws have been highly racialized, and therefore citizenship and naturalization requirements have often worked to support the racial hierarchy of the country (Sáenz and Manges Douglas 2015). Moreover, previous research examining US Latinas/os found that a “citizenship divide” exists as ethnic boundaries are created based on citizenship (Morales, Murga, and Sanchez 2013). That is to say, “ethnic boundaries are formed along citizenship lines, thus constricting the usage of pan-ethnicity as a tool for political mobilizations” (Morales, Murga, and Sanchez 2013:49).…”
Section: The Significance Of Race and Citizenshipmentioning
confidence: 99%
See 1 more Smart Citation